The definition of deviation of “Geoevolutionary” plumb line based on data from the transformation of the Earth - Shylo, Olha; Shylo, Yevhenii (Видавництво Львівської політехніки, 2017)
This article is about dynamic transformation of the litosphere relative to the geoid. Calculated of deviation of “geoevolutionary” plump line, which is interpret as the angle between the normal to the surfaces of ellipsoids approximating the shape of the litosphere and the geoid. These values are converted into tangential force and determine the stress-strain state in the Earth’s crust.
Keywords: the geodynamic evolution of the Earth's; the deflection of the plumb line; transformation of Earth; tangencial forces